2007
DOI: 10.1111/j.1551-2916.2007.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Indentation Response of Fine‐Grained Boron Carbide

Abstract: Boron carbide disks with three different grain sizes were consolidated from submicrometer-sized boron carbide powder using the plasma pressure compaction technique. Static and dynamic indentations were performed to determine their loading-rate dependence on mechanical properties. Dynamic indentations resulted in a decrease in hardness and fracture toughness, and induced more severe damage compared with static indentations. Using Raman spectroscopy, the mechanism responsible for loss of strength under dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 48 publications
(89 reference statements)
5
83
0
1
Order By: Relevance
“…The indentation size effect is probably associated with the strain gradient underneath indenter, which may be different from the one in metals caused by geometrical necessary dislocations. The H and E values of n-B 4 C are comparable to those of microcrystalline B 4 C at similar loads [17][18][19][20] , but less than those of single-crystal B 4 C (ref. 21).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The indentation size effect is probably associated with the strain gradient underneath indenter, which may be different from the one in metals caused by geometrical necessary dislocations. The H and E values of n-B 4 C are comparable to those of microcrystalline B 4 C at similar loads [17][18][19][20] , but less than those of single-crystal B 4 C (ref. 21).…”
Section: Resultsmentioning
confidence: 93%
“…The crack length c is measured from the indentation centre to the tip of the emanated cracks as shown in the Fig. 2c), more than 75% higher than that of microcrystalline B 4 C (refs [18][19][20]24,25). Figure 2d shows the typical Raman spectra collected from the pristine and residual indents at different loading forces.…”
Section: Mechanical Properties and Raman Spectroscopy Analysismentioning
confidence: 97%
“…This loss is attributed to the formation of nanoscale amorphous shear bands (11). The shear amorphization of boron carbide has been confirmed by indentation experiments (12)(13)(14)(15)(16), but a fundamental understanding of the mechanism underlying it has not been fully established. It has been suggested that local shear first breaks the weaker chains and then, displaces and ruptures the stronger icosahedra (16), but recent quantum mechanics (QM) simulations attribute the instability to disintegration of the icosahedra (17,18).…”
mentioning
confidence: 99%
“…The dynamic indentations were conducted using a dynamic indentation hardness tester described in earlier publications by Subhash and co-workers. [16,[19][20][21] The duration of dynamic loading was around 100 ls. The strain rate of indentation was estimated to be above 1000/s.…”
Section: Experimental Methodsmentioning
confidence: 99%